2017
DOI: 10.1088/1674-1056/26/12/128101
|View full text |Cite
|
Sign up to set email alerts
|

Positive gate bias stress-induced hump-effect in elevated-metal metal–oxide thin film transistors

Abstract: Under the action of a positive gate bias stress, a hump in the subthreshold region of the transfer characteristic is observed for the amorphous indium-gallium-zinc oxide thin film transistor, which adopts an elevated-metal metal-oxide structure. As stress time goes by, both the on-state current and the hump shift towards the negative gate-voltage direction.The humps occur at almost the same current levels for devices with different channel widths, which is attributed to the parasitic transistors located at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…However, the mobility of device C decreases to 20.5 cm 2 V −1 s −1 , which should be due to the contribution from the bulk traps in the InGaO layer. In addition, the hump effect and significant negative shifts in V th and V on are also observed in device C . It has been reported that the channel thickness plays a critical role in controlling V th and V on of oxide TFTs .…”
Section: Resultsmentioning
confidence: 81%
“…However, the mobility of device C decreases to 20.5 cm 2 V −1 s −1 , which should be due to the contribution from the bulk traps in the InGaO layer. In addition, the hump effect and significant negative shifts in V th and V on are also observed in device C . It has been reported that the channel thickness plays a critical role in controlling V th and V on of oxide TFTs .…”
Section: Resultsmentioning
confidence: 81%
“…We propose two plausible mechanisms for PBS instability with abnormal behavior after repeated mechanical stress in all directions, as shown in Figure (b). First, the N GD (V o 2+ ) increased by repeated mechanical stress can be gradually drifted into the back channel toward the electric field by positive gate bias to form additional current paths. , It has been reported that additional current paths other than main one (front channel) can degrade in subthreshold regions, such as the hump . Second, when positive gate bias is applied, hydrogen (H + ) may be introduced into mechanically degraded IGZO from Al 2 O 3 G.I.…”
Section: Resultsmentioning
confidence: 99%
“…Under NBTIS and PBTIS, both H and Vo in IZO can absorb the photon and thermal energy and ionize to electrons, thus exhibiting a more significant negative Vth drift than NBS and PBS. Under PBTIS, the hump appears in the transfer characteristic, which may be caused by the trapping of positively charged ionized oxygen vacancy (Vo 2+ ) at the edge of the channel width direction, which has a stronger electric field, thus generating parasitic transistors [12].…”
Section: Methodsmentioning
confidence: 99%